Earth 2 die komplette Serie - Napolitano, Joe 1948-; Duggan, Michael W. (Universal Pictures, 2010)
Embark on the quest to find a new home planet for humanity in the year 2192. A small team puts together an expedition to found a new civilisation 22 light years in the future. But after their ship crash lands on the wrong side of planet G889, the colonists quickly discover that their new home already has some very strange and hostile inhabitants
22 Folgen à 45 Min.
Enth. Outtakes, Deleted Scenes
Keywords: Television series; Science fiction television programs / United States; Space colonies / Drama; Video recordings for the hearing impaired; Life on other planets -- Drama.; Science fiction television programs.; Television programs.; Science fiction films; Außerirdisches Leben; USA; Fernsehserie; DVD-Video